IMPROVING STUDENTS' CULTURAL AND CIVIC LITERACY THROUGH EDUCATIONAL POSTER PROJECT IN GRADE V - Rezania, Vanda; Wachidah, Kemil; Asmara Cahyani Hayuningrat, Dewi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to improve the cultural and civic literacy of grade V students through the implementation of educational poster projects as contextual and interesting learning media. The background of this study is the low level of cultural and civic literacy of students, as identified from the initial test results in class V of SDN Krian 2. Most students showed a low understanding of cultural and civic values, which was allegedly caused by the lack of connection between the material and meaningful learning activities. Method: This study used the Kurt Lewin model of Classroom Action Research (PTK) method implemented in two cycles, with the stages of planning, action, observation, and reflection. The research subjects were 29 fifth grade students. The instrument used was a test to measure the level of cultural and civic literacy before and after the implementation of the action. Result: The results showed a significant increase, from 55.5% in the pre-cycle (poor category), to 78.5% after Cycle I, and increased again to 86% in Cycle II (good category). Novelty: The novelty in this study lies in the use of educational poster media as a project-based learning approach that is able to improve cultural and civic literacy in grade V students.